A coupled thermo‐poro‐mechanical model of the breast applied to breast cancer detection. Issue 1 (17th December 2018) - Niedermeyer, Angela; Ma, Songyun; Markert, Bernd
Abstract: Recently, diagnostic methods based on infrared thermographic imaging of the skin have shown promising results regarding skin cancer detection. The application to breast cancer has not yet led to satisfying results. The challenge lies in determining the location and intensity of the embedded cancerous heat source from measured infrared radiation of the breast surface. For this purpose, a coupled poro‐thermo‐mechanical constitutive model of the breast is proposed here, which describes the energy transport in this soft tissue. In this work, numerical simulations of a breast model containing a tumor are conducted to study the correlation between skin temperature and tumour characteristics. The results demonstrate that the proposed modelling approach can be employed to determine optimal measurement conditions such as surrounding temperature and to evaluate the potentialities of transient measurements.